2018
DOI: 10.1534/genetics.117.300377
|View full text |Cite
|
Sign up to set email alerts
|

Protein Moonlighting Revealed by Noncatalytic Phenotypes of Yeast Enzymes

Abstract: A single gene can partake in several biological processes, and therefore gene deletions can lead to different-sometimes unexpected-phenotypes. However, it is not always clear whether such pleiotropy reflects the loss of a unique molecular activity involved in different processes or the loss of a multifunctional protein. Here, using metabolism as a model, we systematically test the null hypothesis that enzyme phenotypes depend on a single annotated molecular function, namely their catalysis. We screened a set o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…An illustrative example is the recent study of Espinosa-Cantú and colleagues, in which they experimentally addressed the prevalence of enzymes with moonlighting functions in Saccharomyces cerevisiae [12]. They evaluated if the enzyme gene deletion phenotypes are caused solely by the loss of catalytic activity, or to a yet unknown moonlighting function independent of the catalytic activity [12]. This study showed that 4 out of 11 tested enzymes may have moonlighting functions, thus suggesting that moonlighting proteins may be highly prevalent.…”
Section: Experimental Approaches To Detect Moonlighting Proteinsmentioning
confidence: 99%
“…An illustrative example is the recent study of Espinosa-Cantú and colleagues, in which they experimentally addressed the prevalence of enzymes with moonlighting functions in Saccharomyces cerevisiae [12]. They evaluated if the enzyme gene deletion phenotypes are caused solely by the loss of catalytic activity, or to a yet unknown moonlighting function independent of the catalytic activity [12]. This study showed that 4 out of 11 tested enzymes may have moonlighting functions, thus suggesting that moonlighting proteins may be highly prevalent.…”
Section: Experimental Approaches To Detect Moonlighting Proteinsmentioning
confidence: 99%
“…The molecular activities of a moonlighting protein are usually described as unrelated to each other and independently of the primary sequence (Huberts and van der Klei, 2010;Flores and Gancedo, 2011). Indeed, experimental evidence for the characterization of a moonlighting protein is mostly provided by mutants that are defective in one molecular function without affecting the others (Jeffery, 2009;Gancedo et al, 2016;Espinosa-Cantu et al, 2018). In the case of yeast Ure2, mutants without nitrogen-catabolite repression activity maintain their enzymatic capacities ( Figure 1D).…”
Section: Moonlighting Proteins Multitask In Disparate Functionsmentioning
confidence: 99%
“…Moonlighting proteins with different molecular and functional characteristics have been described in a wide variety of organisms and the number of examples has increased in the last few years to almost 700 carefully curated moonlighting proteins (Hernández et al, 2014;Mani et al, 2015;Chen et al, 2018;Franco-Serrano et al, 2018b). Even though experimental setups have been aimed at revealing protein moonlighting in an unbiased manner (Su and Pillus, 2016;Espinosa-Cantu et al, 2018), still most known cases have been described by serendipity, either by studying a single protein in an exhaustive manner (e.g., the delta-crystalline Piatigorsky and Horwitz, 1996) or as rather surprising results from functional screens (Zelenaya-Troitskaya et al, 1995;Hall et al, 2004;Chen et al, 2005;Scott and Pillus, 2010;Scherrer et al, 2010;Chang et al, 2012).…”
Section: Moonlighting Proteins Multitask In Disparate Functionsmentioning
confidence: 99%
See 2 more Smart Citations